Data Needs for Policy Research on State-Level Health Insurance Markets - Kosali Simon (SAGE Publishing, 2008)
Private and public health insurance provision in the United States operates against a backdrop of 50 different regulatory environments in addition to federal rules. Through creative use of available data, a large body of research has contributed to our understanding of public policy in state health insurance markets. This research plays an important role as recent trends suggest states are taking the lead in health care reform. However, several important questions have not been answered due to lack of data. This paper identifies some of these areas, and discusses how the Agency for Healthcare Research and Quality could push the research agenda in state health insurance policy further by augmenting the market-level data available to researchers. As states consider new forms of regulation and assistance for their insurance markets, there is increased need for better warehousing and maintenance of policy databases.